Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To determine the radius of the circle given by the equation [tex]\(x^2 + y^2 - 2x + 8y - 47 = 0\)[/tex], we need to rewrite the equation in the standard form of a circle's equation, [tex]\((x - h)^2 + (y - k)^2 = r^2\)[/tex], where [tex]\((h, k)\)[/tex] is the center of the circle and [tex]\(r\)[/tex] is its radius.
We can achieve this by completing the square for both the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms.
1. Group the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms together:
[tex]\[ x^2 - 2x + y^2 + 8y = 47 \][/tex]
2. Complete the square for the [tex]\(x\)[/tex] terms:
[tex]\[ x^2 - 2x \][/tex]
To complete the square:
- Take the coefficient of [tex]\(x\)[/tex], which is [tex]\(-2\)[/tex], divide by 2 and square it: [tex]\(\left(\frac{-2}{2}\right)^2 = 1\)[/tex].
- Add and subtract this square inside the equation:
[tex]\[ x^2 - 2x + 1 - 1 = (x - 1)^2 - 1 \][/tex]
3. Complete the square for the [tex]\(y\)[/tex] terms:
[tex]\[ y^2 + 8y \][/tex]
To complete the square:
- Take the coefficient of [tex]\(y\)[/tex], which is [tex]\(8\)[/tex], divide by 2 and square it: [tex]\(\left(\frac{8}{2}\right)^2 = 16\)[/tex].
- Add and subtract this square inside the equation:
[tex]\[ y^2 + 8y + 16 - 16 = (y + 4)^2 - 16 \][/tex]
4. Substitute the completed squares back into the equation:
[tex]\[ (x - 1)^2 - 1 + (y + 4)^2 - 16 = 47 \][/tex]
5. Combine and simplify the constants on the right side:
[tex]\[ (x - 1)^2 + (y + 4)^2 - 17 = 47 \][/tex]
[tex]\[ (x - 1)^2 + (y + 4)^2 = 47 + 17 \][/tex]
[tex]\[ (x - 1)^2 + (y + 4)^2 = 64 \][/tex]
Now we have the equation in the standard form:
[tex]\[ (x - 1)^2 + (y + 4)^2 = 64 \][/tex]
From this, we can see that the radius [tex]\(r\)[/tex] of the circle is:
[tex]\[ r^2 = 64 \implies r = \sqrt{64} = 8 \][/tex]
Thus, the radius of the circle is:
[tex]\[ \boxed{8} \text{ units} \][/tex]
We can achieve this by completing the square for both the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms.
1. Group the [tex]\(x\)[/tex] and [tex]\(y\)[/tex] terms together:
[tex]\[ x^2 - 2x + y^2 + 8y = 47 \][/tex]
2. Complete the square for the [tex]\(x\)[/tex] terms:
[tex]\[ x^2 - 2x \][/tex]
To complete the square:
- Take the coefficient of [tex]\(x\)[/tex], which is [tex]\(-2\)[/tex], divide by 2 and square it: [tex]\(\left(\frac{-2}{2}\right)^2 = 1\)[/tex].
- Add and subtract this square inside the equation:
[tex]\[ x^2 - 2x + 1 - 1 = (x - 1)^2 - 1 \][/tex]
3. Complete the square for the [tex]\(y\)[/tex] terms:
[tex]\[ y^2 + 8y \][/tex]
To complete the square:
- Take the coefficient of [tex]\(y\)[/tex], which is [tex]\(8\)[/tex], divide by 2 and square it: [tex]\(\left(\frac{8}{2}\right)^2 = 16\)[/tex].
- Add and subtract this square inside the equation:
[tex]\[ y^2 + 8y + 16 - 16 = (y + 4)^2 - 16 \][/tex]
4. Substitute the completed squares back into the equation:
[tex]\[ (x - 1)^2 - 1 + (y + 4)^2 - 16 = 47 \][/tex]
5. Combine and simplify the constants on the right side:
[tex]\[ (x - 1)^2 + (y + 4)^2 - 17 = 47 \][/tex]
[tex]\[ (x - 1)^2 + (y + 4)^2 = 47 + 17 \][/tex]
[tex]\[ (x - 1)^2 + (y + 4)^2 = 64 \][/tex]
Now we have the equation in the standard form:
[tex]\[ (x - 1)^2 + (y + 4)^2 = 64 \][/tex]
From this, we can see that the radius [tex]\(r\)[/tex] of the circle is:
[tex]\[ r^2 = 64 \implies r = \sqrt{64} = 8 \][/tex]
Thus, the radius of the circle is:
[tex]\[ \boxed{8} \text{ units} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.